Memahami Prinsip Kerja Kapitalisme dalam Invasi Rusia terhadap Ukraina - Alfian Tri Laksono; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
The world political situation is sometimes difficult to predict. Tensions between major countries often raise global concerns which are feared to trigger collective chaos which seriously endangers human existence on this earth. However, what do you mean by these concerns "granted" by Putin's decision to invade Ukraine? Various kinds of motives and reasons indeed surround the event. However, in particular, the economic justification becomes one thing that stands out compared to other motives. Therefore, this study aims to analyse the working principle of the economic system, namely capitalism during the Russian invasion of Ukraine. The method used is qualitative with the type of literature study. The results achieved in this study are that this war brought fresh air to Russia which managed to gain financially during this trade. This advantage stems from Putin's response which stopped sending energy resources to countries that dared to oppose it, especially the European Union. So sales were diverted to Asian countries with a larger sales scale and a payment system adapted to the Russian currency.